Cordycepin attenuates migration and invasion of HSC-4 oral squamous carcinoma cells through autophagy-dependent FAK/Akt and MMP2/MMP9 suppression - Thunwa Binlateh; Nawapol Uppatcha; Jutamast Thepchai; Yanaphat Pleungtuk; Parinya Noisa; Pilaiwanwadee Hutamekalin; Paiboon Jitprasertwong (Elsevier, 2022)
Background/purpose: Cordycepin has been proposed anti-cancer effects, however, it is unclear whether and how cordycepin affects oral squamous carcinoma cell (OSCC) migration and invasion. This study aimed to investigate the effect of cordycepin on migration and invasion of OSCC (HSC-4 cells), and its underlying mechanism. Materials and methods: Cell viability was measured with MTT assay. Migrative and invasive abilities were determined by scratch wound healing, agarose spot and transwell invasion assays, respectively. Monodasylcadaverine (MDC) staining, immunofluorescence staining of LC3 and RT-PCR evaluated the gene expression of LC3 and p62 were applied to investigate autophagy. MMP2 and MMP9 gene expression and activity were examined by RT-PCR and gelatin zymography. Expression of caspase 3, cleaved caspase 3, FAK, p-FAK, Akt and p-Akt was determined by Western blot. Results: Cordycepin significantly inhibited HSC-4 cell migration and invasion in a concentration-dependent manner. Cordycepin treatment caused an induction of autophagy, as evidenced by increased MDC fluorescence intensity and MDC positive cells, and upregulated expression level of LC3 gene. In addition, inhibition of autophagy by chloroquine (CQ) significantly abolished cordycepin-inhibited HSC-4 cell migration and invasion, demonstrating that cordycepin-inhibited migration and invasion was mediated by autophagy. Mechanistic studies showed that cordycepin significantly suppressed FAK and Akt phosphorylation, and MMP2 and MMP9 activities. Conversely, CQ pre-incubation significantly restored its expression and activity in cordycepin-treated cells. Conclusion: Cordycepin induces autophagy to suppress FAK and Akt phosphorylation, and MMP2 and MMP9 activity, which responsible for the attenuation of HSC-4 cell migration and invasion.